Assessing the Role of State and Local Public Health in Outreach and Enrollment for Expanded Coverage: A Case Study on New Orleans, Louisiana - Williams, Malcolm V. (Rand Health Q, 2017)
The Patient Protection and Affordable Care Act (ACA) laid the groundwork for a substantial increase in the number of people who have access to health insurance through Medicaid expansion or health insurance marketplaces. During the first open-enrollment season, states used a variety of strategies to reach out to and enroll newly eligible people. Typically, they used federal and state funding to develop navigator programs. Program design differed by location, and, although many stakeholders were involved in these efforts, state and local health departments (LHDs) were, and remain, a relatively untapped resource. This article is one in a series designed to highlight innovative models and best practices that leverage LHD involvement in ACA outreach and enrollment and to facilitate knowledge transfer to other geographic regions looking to leverage the full range of roles for LHDs in ACA outreach and enrollment. Each case study was designed to capture nuanced differences in how health departments support these efforts in their communities, identify facilitators and barriers to these approaches, and develop lessons learned from these activities. These studies identify compelling models for how state and local health departments can implement similar activities in their own communities. Further, they provide guidance and insight into the role LHDs can play now, and help redefine that role in the future, as states continue to enroll residents in health insurance coverage moving forward. This article focuses on a case study on New Orleans, Louisiana.